Manajemen Penerapan Digital Marketing pada Ice Cream Momoyo di Kota Bandar Lampung - Komariah, Rizka (STIES ALIFA, 2024)
Digital marketing is a marketing strategy used in a business in providing goods, services and services using technological devices and the internet in its promotional treatment. Digital marketing is currently trending and widely used in business, there are even some businesses that only use digital marketing in their promotions or do not use other conventional media. With the development of cafe businesses and the like, Momoyo has emerged with various ice cream product offerings that must compete with similar product competitors. The purpose of the study is to determine the management and application of digital marketing in Momoyo ice cream. Qualitative descriptive is the method chosen in this study with purposive sampling as a sample selection technique while the analysis tool uses IMA. The conclusion that can be drawn is that the marketing management used by Momoyo is very large through digital marketing. The form of digital marketing used is utilizing social media as the main marketing platform. The strategy is to post content and promote Momoyo products, as well as collaborating with influencers and celebrities for marketing.